Toxicity from fluoropolymer-containing grout, tile and stone floor sealants reported to the UK National Poisons Information Service 2009–2015. (3rd July 2017) - Henke, Des; Campbell, Alex; Bradberry, Sally M.; Sandilands, Euan A.; Thomas, Simon H. L.; Thompson, John P.; Vale, J. Allister
Abstract: Context: Grout, tile and floor stone sealants contain a solvent, a water-repelling agent and in the case of aerosols a propellant. The water-repelling agent used is typically a fluoropolymer resin, a silicon-based resin, or a combination of both. Objective: To report the clinical course in patients exposed to fluoropolymer-containing sealants referred to the United Kingdom National Poisons Information Service. Methods: A retrospective analysis was performed of telephone enquiries received between 2009 and 2015. Results: 101 enquiries involving 96 exposures were received. The majority of the exposures ( n  = 88) occurred when the sealant was delivered from an aerosol. Twelve patients were exposed occupationally and the remainder were exposed while using the product at home. Eighty-nine exposures were as a result of inhalation alone, two followed ingestion, three skin contact and one eye contact; one involved inhalation and eye contact. All 90 patients exposed by inhalation developed clinical features: 31 had a World Health Organisation/International Programme on Chemical Safety/European Commission/European Association of Poison Centres and Clinical Toxicologists Poisoning Severity Score of 1 (minor toxicity), 51 patients had features of moderate toxicity (PSS 2) and eight were graded PSS 3 (severe poisoning). The most common features were dyspnea ( n  = 52; 57.8%; 95% CI = 47.0–68.5), chest pain/tightness ( n  = 34; 37.8%; 95% CI = 27.2–48.4), coughing ( n  = 27; 30.0%; 95% CI = 20.0–40.0) and sinus tachycardia ( n  = 11; 12.2%; 95% CI = 4.1–18.2); hypoxemia was present in 20 (22.2%; 95% CI = 13.1–31.4). At the time of the enquiry a chest X-ray had been performed on 15 patients: in eight patients (all of whom were PSS 3) the X-ray was reported as being abnormal and showed bilateral shadowing. Conclusions: This study demonstrates that if fluoropolymer-containing sealants are inhaled then clinical features may occur and in a small proportion (9%) these features may be severe.